Development, Formulation And Evaluation Of Antihypertensive Transdermal Niosomal Gel - L. Narwade, Vaibhav; Sonawane, Kajol; Kale, Vijaykumar; Thakare, Mahesh; Mudgulkar, Supriya (Journal of Neonatal Surgery, 2025)
The present study focuses on the development and evaluation of a transdermal niosomal gel formulation of an antihypertensive drug to overcome the limitations associated with oral administration. Niosomes, composed of non-ionic surfactants and cholesterol, were prepared using the modified ether injection method and optimized based on particle shape and entrapment efficiency. The optimized batch (N1) demonstrated spherical vesicles with high drug entrapment and content. Further, the niosomal suspension was incorporated into Carbopol 934 gel to develop transdermal gel formulations (N5–N8) with varying drug concentrations. These formulations were evaluated for physical characteristics including pH, viscosity, consistency, clarity, drug content, entrapment efficiency, and in-vitro drug release using Franz diffusion cells. Among all batches, N8 showed superior performance with 93.80% drug content and 81.14% cumulative drug release at 24 hours, along with desirable physicochemical properties. Stability studies over 30 days confirmed the formulation's integrity under different storage conditions. The results suggest that niosomal gel is a promising transdermal delivery system for sustained and effective delivery of antihypertensive drugs, offering improved bioavailability and patient compliance...